Promoting physical activity for disabled people who are ready to become physically active: A systematic review. (July 2018) - Jaarsma, Eva Annika; Smith, Brett
Abstract: Objective: To provide an overview of which psychosocial factors are related to physical activity participation for disabled people who intend to be active, to determine which interventions effectively improved physical activity and to identify how participants were described as intenders. Design: A systematic review was conducted using PRISMA guidelines. Method: Six databases were searched using MesH terms and free texts. Inclusion criteria were studies focusing on disabled people, physical activity and intention. Exclusion criteria were studies not including disabled people, focusing on children or on biomechanical or neurological aspects of physical activity. Included studies were appraised using the quality tool by Sirriyeh et al, 2012 and were coded using the behaviour change technique (BCT) taxonomy by Michie et al. (2011). BCTs were considered effective if they were present in at least 50% of the effective studies included in this review and only present in one of the non-effective studies, as described in Hynynen et al. (2016). Results: Twenty studies were included in this review. Self-efficacy, intention and weighing pros and cons were positively associated with physical activity, whereas experiencing barriers and severity of the impairment were negatively associated. Intervention studies reported BCTs such as self-monitoring of behaviour, barrier identification/problem solving and action planning as effective elements of interventions. Conclusions: Future research should consider including the above mentioned techniques as well as additional BCTs to provide better insight in effective elements promoting physical activity of disabled intenders. We close with a series of recommendations for future research. Highlights: We need more longitudinal studies to determine the causality between physical activity and variables such as self-efficacy. Researchers should consider also describing the participant's stage of intention. Behaviour change techniques such as action planning should be included as elements in intervention studies. Researchers need to provide a clearer description of the content of the physical activity interventions. Researchers need to conduct more community led research to meet the needs of people and improve successful implementation.